2005
DOI: 10.1111/j.1365-2699.2004.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Cladistic analysis of distributions and endemism (CADE): using raw distributions of birds to unravel the biogeography of the South American aridlands

Abstract: Aim  To use published distributional and taxonomic information on Neotropical birds in a cladistic analysis of distributions and endemism (CADE) to generate a testable hypothesis of area‐relationships for the arid areas of endemism, particularly those of Central South America (the ‘arid diagonal’), and to clarify the different methodologies commonly associated with parsimony analysis of endemicity (PAE). Location  South America. Methods  Cladistic analysis of distributions and endemism. Results  We obtain a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
123
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(143 citation statements)
references
References 52 publications
(122 reference statements)
14
123
1
5
Order By: Relevance
“…The lack of resolution on grouping provinces from Chacoan and Parana subregions in a polytomic clade can clearly be associated with Sepedonea species dependent on wet vegetation that are distributed over open vegetation areas. Especially in the Cerrado, PORZECANSKI & CRACRAFT (2005) concluded that the presence of forest-dependent species in that region would be the main factor influencing the polytomic outcome of the Atlantic forest and South America's arid areas (Cerrado, Chaco and Caatinga) in their study.…”
Section: Relationships Between Areas Of Endemism In the Neotropical Rmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of resolution on grouping provinces from Chacoan and Parana subregions in a polytomic clade can clearly be associated with Sepedonea species dependent on wet vegetation that are distributed over open vegetation areas. Especially in the Cerrado, PORZECANSKI & CRACRAFT (2005) concluded that the presence of forest-dependent species in that region would be the main factor influencing the polytomic outcome of the Atlantic forest and South America's arid areas (Cerrado, Chaco and Caatinga) in their study.…”
Section: Relationships Between Areas Of Endemism In the Neotropical Rmentioning
confidence: 99%
“…The Neotropical region is a good example of this intricate biogeographical pattern, and this is evident in various hypotheses about relationships between areas of endemism. The different hypotheses lend themselves to different explanatory proposals (CRACRAFT & PRUM 1988, PRUM 1988, AMORIM & PIRES 1996, SILVA & OREN 1996, BATES et al 1998, MORRONE & COSCARÓN 1998, RON 2000, MARKS et al 2002, PORZECANSKI & CRACRAFT 2005, BORTOLANZA et al 2006, HUBERT & RENNO 2006, NIHEI & CARVALHO 2007.…”
Section: Final Considerations: the Incongruence Of Branching Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that, we decided to employ also methodologies that do not rely directly on phylogenetic data, such as CADE and PAE but which nonetheless may be discussed and tested in comparisons with results from cladistic biogeographic analyses (Porzecanski, Cracraft, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A literatura é rica em dados sobre esse conceito e sobre as dificuldades de como estima-lo (Walther & Morand 1998, Hellmann & Fowler 1999, Gotelli & Colwell 2001, Ackerman et al 2007, Smidt et al 2007. O conceito de endemismo foi também amplamente discutido para diversos táxons em diversas áreas geográficas, tanto para quantificá-lo (Usher 1986, Kerr 1997) como para comparar uma régião à outra (Ron 2000, Bisconti et al 2001, Linder et al 2005, Porzecanski & Cracraft 2005, Moreno et al 2006. O presente estudo se baseia na avaliação destes dois conceitos, riqueza e endemismo, para o gênero Baptistonia Barb.…”
Section: Introductionunclassified